The role of an external facilitator in developing new co-creation platforms in university education - Tiina Tuulos; Ville Taajamaa; Meri Vainio (Finland, 2022)
Previous studies suggest that change in education is often initiated with the recruitment of an external facilitator, faculty with industry experience or newly hired faculty replacing those retiring [1,2]. The main interests of this study are twofold: what role does an external facilitator have in a change process and to discuss whether new development should be initiated, sustained and facilitated from within the organization or by an external change agent.
This paper relies on two case studies, one in Austria and one China. Firstly, a case study on an environment supporting an interdisciplinary product development course hosted by a University of Technology in Austria. And secondly, a case study of Sino-Finnish Centre, a collaboration platform between a Finnish and Chinese university. The aims of both cases were essentially similar: to create new practices, a collaborative learning environment and more student-centric culture based on an existing experiential learning platform. In both the change was initiated with a recruitment of an external facilitator. However, the starting points varied significantly: in China the intention was to form a formal strategic partnership between the two universities and the new platform was supposed to be the tangible collaboration environment, whereas in Austria the interest was to create a more student-centric and vibrant atmosphere and a supporting environment around an interdisciplinary product development course.
SEFI conference 2016 "Engineering Education on Top of the World: Industry University Cooperation"